2015
DOI: 10.1021/acs.jnatprod.5b00600
|View full text |Cite
|
Sign up to set email alerts
|

Avertoxins A–D, Prenyl Asteltoxin Derivatives from Aspergillus versicolor Y10, an Endophytic Fungus of Huperzia serrata

Abstract: Aspergillus versicolor Y10 is an endophytic fungus isolated from Huperzia serrata, which showed inhibitory activity against acetylcholinesterase. An investigation of the chemical constituents of Y10 led to the isolation of four new prenylated asteltoxin derivatives, named avertoxins A-D (2-5), together with the known mycotoxin asteltoxin (1). In the present study, we report structure elucidation for 2-5 and the revised NMR assignments for asteltoxin and demonstrated that avertoxin B (3) is an active inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…In addition; compound 2 also exhibited inhibitory activity against H1N1 with IC 50 value of 3.5˘1.3 µM. Compounds 2 and 3 were published online on 30 November 2015 as new compounds after the date we submitted on 2 November 2015 [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition; compound 2 also exhibited inhibitory activity against H1N1 with IC 50 value of 3.5˘1.3 µM. Compounds 2 and 3 were published online on 30 November 2015 as new compounds after the date we submitted on 2 November 2015 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al (2014) has reported A. versicolor from rhizome of Paris marmorata [43]. A. versicolor has also been isolated from Chinese medicinal plant Huperzia serrata [44].…”
Section: Isolation and Identification Of Endophytic Fungimentioning
confidence: 99%
“…Aspergillus versicolor is a chemically brilliant fungal species with immense potential to produce a wide range of unique secondary metabolites including alkaloids [1,2,3], polyketides [4,5,6], and terpenoids [7]. Some of these metabolites exhibit intriguing biological properties, including antimicrobial properties [3,5] and cytotoxicity [6] as well as enzyme-inhibiting activities [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these metabolites exhibit intriguing biological properties, including antimicrobial properties [3,5] and cytotoxicity [6] as well as enzyme-inhibiting activities [1,4]. …”
Section: Introductionmentioning
confidence: 99%